Bronchiolar adenoma/ciliated muconodular papillary tumor mixed with adenocarcinoma in situ in the same tumor - Suiha Uchiyama; Kenichi Mizutani; Eriko Suzuki; Naoko Yoshii; Takuya Watanabe; Hiroyuki Tsuchida; Shogo Yobita; Kensuke Iguchi; Minori Nakamura; Takumi Endo; Seishiro Takahashi; Hiroshi Ogawa; et al. (Thoracic Cancer, 2023)
Abstract Bronchiolar adenoma (BA)/ciliated muconodular papillary tumor (CMPT) is defined as a benign tumor composed of epithelial and basal cells. Recently, some cases with driver mutations or malignant transformation have been observed. Thus, whether BA/CMPT is benign or malignant remains controversial. We herein report an extremely rare case of a 68‐year‐old woman with a CMPT accompanied by adenocarcinoma in situ (AIS). BA/CMPT existed inside the AIS. The BA/CMPT component did not show any driver mutations; however, the AIS component had an EGFR driver mutation in exon 19. The accumulation of cases and further studies are needed to discuss the malignant potential of BA/CMPT.